The effect of dosage of vermicompost and biourine plus on growth and yield of organic shallot (Allium ascalonicum L.) - Qibtiyah, Mariyatul; Istiqomah, Istiqomah; Sunarto, Sunarto (Environmental and Agriculture Management, 2024)
Shallot is a common horticultural crop, providing a number of benefits. Effect of organic manure and liquid organic fertilizer and their interaction on growth and yield of shallot was studied. The purpose of this study was to determine the effectiveness increase organic shallot yield with dose fertilizer vermicompost and biourine plus. A two factor experiment with three replications, arranged in factorial randomized block design, was carried out. First factor was dose of vermicompost i.e without vermicompost, vermicompost 10 t/ha, vermicompost 15 t/ha. Second factor was dose of biourine Plus i.e without biourine plus, biourine plus 1500 l/ha, biourine plus 2000 l/ha. Observed variables were height plants, numbers of leaves, number of tubers, fresh weight of tuber, and dry tuber weight. Data were analysed by F test followed by LSD at 5%. It was concluded that the vermicompost and biourine plus dose treatment produced a significant impact on plant height and number of shallot leaves but had no effect on shallot yields. Vermicompost 15 t/ha is able to increase the harvest weight of shallots (fresh weight) by 14% and increase the dry weight of tubers by 17.45%.